A virtual laboratory system for physiology teaching - KArl Bohme; Geoff Brindle; Len Seal; William Mitchell (Association for Learning Technology, 1995)
There exist a number of areas in the teaching of physiology which potentially lend themselves to a Computer-Based Learning approach. One such area which has been explored at Manchester Metropolitan University (MMU) and elsewhere (Dewhurst, 1993; Kwan, 1993) is the use of multimedia tools to simulate aspects of experiments traditionally performed on animals. The use of real animal specimens (for example, frogs or rats) for dissection and experimentation is both costly and contrary to the ethics of some students.